Instrumentation Reference Book (3rd Edition) - Boyes, Walt (Elsevier, 2003)
Often categorized as either 'techniques' or 'applications' this book addresses the various applications that may be needed with reference to the practical techniques that are available for the instrumentation or measurement of a specific physical quantity or quality. This book is a comprehensive and authoritative collection of technical information, which is of direct practical value to instrumentation and control engineers as well as all instrument technicians and users. It is also an indispensable addition to any academic library for the benefit of engineering and science students.